2008
DOI: 10.1109/jlt.2008.922193
|View full text |Cite
|
Sign up to set email alerts
|

Design Rules for Single-Mode and Polarization-Independent Silicon-on-Insulator Rib Waveguides Using Stress Engineering

Abstract: Abstract-There is a trend towards miniaturization of silicon photonic circuits due to superior performance and small cost. Design rules that must be imposed on the geometry of optical waveguides to make them behave as polarization-independent and singlemode devices are well known for waveguides with relatively large cross sections and for some small cross-sectional rib waveguides with vertical sidewalls and an air top cladding. The influence of the top oxide cover on waveguide birefringence was analyzed recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Field profile is strongly dependent on the waveguide geometry, and in some cases we found that the more critical higher-order mode was the quasi-TM 01 mode, while in other cases it was the quasi-TM 10 . In common with our previous work [24,25], we found that satisfying the single-mode condition (SMC) for the TM mode is again more restrictive than for the TE mode. The area below the SMC for quasi-TM mode defines the global condition for the single-mode behavior.…”
Section: Single-mode and Polarization-independent Waveguidessupporting
confidence: 85%
“…Field profile is strongly dependent on the waveguide geometry, and in some cases we found that the more critical higher-order mode was the quasi-TM 01 mode, while in other cases it was the quasi-TM 10 . In common with our previous work [24,25], we found that satisfying the single-mode condition (SMC) for the TM mode is again more restrictive than for the TE mode. The area below the SMC for quasi-TM mode defines the global condition for the single-mode behavior.…”
Section: Single-mode and Polarization-independent Waveguidessupporting
confidence: 85%
“…In spite of its similarity to previously reported results on the TM-like control of the SMC of deeply-etched small rib waveguides (Chan et al 2005), distinct differences apply. These differences include the contribution of the minor transverse field components of these rib guides to their modal cutoff as well as the stress-induced birefringence caused by the upper cladding layer Milosevic et al 2008). …”
Section: Symmetric Profilesmentioning
confidence: 99%
“…Single-mode and polarization-independence are desirable conditions for optical waveguides [1][2][3][4][5][6]. Single-mode operation is necessary to avoid signal distortion due to different mode group velocities.…”
Section: Introductionmentioning
confidence: 99%
“…Single-mode and polarization-independent waveguides have been reported for silicon-oninsulator (SOI) rib waveguides [1,2] and with rib waveguides having sidewall angles [4]. Single-mode and polarization-independent propagation based on SOI rib waveguides and photonic wires has been investigated at the submicron scale [3].…”
Section: Introductionmentioning
confidence: 99%